2017
DOI: 10.1080/0142159x.2017.1315075
|View full text |Cite
|
Sign up to set email alerts
|

Overarching challenges to the implementation of competency-based medical education

Abstract: Medical education is under increasing pressure to more effectively prepare physicians to meet the needs of patients and populations. With its emphasis on individual, programmatic, and institutional outcomes, competency-based medical education (CBME) has the potential to realign medical education with this societal expectation. Implementing CBME, however, comes with significant challenges. This manuscript describes four overarching challenges that must be confronted by medical educators worldwide in the impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
120
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 35 publications
0
120
0
2
Order By: Relevance
“…Developing effective training programs and staff development to support the implementation of CBA for tutors is a crucial factor when moving toward a competency‐based approached (Lowrie, Smith, & Hill, ; Smith, ). Therefore, underpinning the development of the training program discussed in this case study are two principles: ensuring tutors are appropriately briefed (Caverzagie et al., ; Hoogveld, Paas, & Jochems, ; Smith, ) and that traditionalists understand the potential benefits of CBA (Ferguson, Caverzagie, Nousiainen, & Snell, ).…”
Section: Project Backgroundmentioning
confidence: 99%
“…Developing effective training programs and staff development to support the implementation of CBA for tutors is a crucial factor when moving toward a competency‐based approached (Lowrie, Smith, & Hill, ; Smith, ). Therefore, underpinning the development of the training program discussed in this case study are two principles: ensuring tutors are appropriately briefed (Caverzagie et al., ; Hoogveld, Paas, & Jochems, ; Smith, ) and that traditionalists understand the potential benefits of CBA (Ferguson, Caverzagie, Nousiainen, & Snell, ).…”
Section: Project Backgroundmentioning
confidence: 99%
“…Finally, as the shift toward competency-based medical education progresses, there is a need to explore the new technologies that will help feasibly establish and assess competency. 35,36 The learning platform presented in this research demonstrated effectiveness for training on clinical tasks with dichotomous outcomes. Where the assessment is more complex, our model could be adapted to address unique training needs for different types of clinical tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a change in the current “one size fits all' approach could possibly ease some of the burden in clinical training and maintain the important goal of graduating students who are competent professionals. However, this shift would not be without its own challenges which include the need to: (a) align all regulatory stakeholders so that they support competency‐based progression; (b) redesign clinical education; (c) determine expected outcomes for individuals, programs, and training institutions so that performance can be measured; and (d) establish a culture of mutual accountability for the achievement of these defined outcomes (Caverzagie et al, ).…”
Section: Genetic Counseling Training Program Accreditationmentioning
confidence: 99%